Effect of organic solvent vapor treatment on transistor performance and contact resistance of copper phthalocyanine based organic field-effect transistors. (February 2021) - Kumar, Pankaj; Yadav, Sarita; Kumar, Naresh; Kumar, Lokendra
Highlights: Thermally evaporated CuPc thin film on SiO2 / n++ Si substrate used as active layer for OFET fabrication. The active layer was modified with organic solvent treatment. OFETs performance enhancement due to reformed surface and contact resistance. The best result was achieved for solvent vapor annealed devices with on/off ratio of 10 3 and carrier mobility of 2.6 × 10 −3  cm 2 /Vs. Abstract: In this study, we investigated the effect of organic solvent drop-casting and solvent vapor annealing (SVA) on the surface morphology of copper phthalocyanine (CuPc) thin film and its effect on contact resistance in organic field effect transistors (OFETs). Organic solvents: acetone and isopropyl alcohol (IPA) are used for drop-casting and SVA treatment of CuPc film. The morphology, crystallinity and optical properties of untreated and treated CuPc films are investigated through ultraviolet–visible (UV–Vis) absorption spectroscopy, X-ray diffraction (XRD) and atomic force microscopy (AFM). The results reveal that crystallinity and grain size increase in CuPc film treated with SVA. Large grain size results fewer grain boundaries forming better contact between source/drain (S/D) electrodes and the organic layer. As a result, the SVA treated CuPc based OFETs show one order increased charge carrier mobility and two order decreased contact resistance compared to that observed in untreated CuPc based OFET.